1994
DOI: 10.1017/s0260305500010922
|View full text |Cite
|
Sign up to set email alerts
|

The elastic modulus of columnar-grain fresh-water ice

Abstract: ABSTRACT. An analysis is presented of stress and strain meas urements mad e during a n investiga ti on of th e ch aracteri sti cs of cracks form ed in column a r-g ra in , type S2, fr es h-water ice 5 during uni axial , compressive loading a t th e nominal strain ra tes of 10 3, 10 4 a nd 10 S i , and temperatures of _5°, -10°, -20° a nd -30°C. Th e a na lysis hows th a t for this range of strain rate and temperature, ice behaves as a n a nelas ti c so lid. R es ults are given for th e tim e, g rain -size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…He also found that for total strain of 6 x 10-4 to 9 x 10-\ applied in the constant-strain-rate tests, the proportion of grain-boundary cracks decreased from about 100% at the nominal strain rate of 10 2 s I, to about 65% at the nominal rate of 10-5 s-I. The delayed elastic component of the strain increased with decreasing strain rate and there was a significant plastic component at the nominal rate of 10 5 s I (Gold, 1994). In summary, the occurrence of the maxima ",,'ith decreasing strain rate is associated with an increasing proportion of trans crystalline cracks and an increasing delayed elastic and plastic strain.…”
Section: Spatial Distributionmentioning
confidence: 89%
“…He also found that for total strain of 6 x 10-4 to 9 x 10-\ applied in the constant-strain-rate tests, the proportion of grain-boundary cracks decreased from about 100% at the nominal strain rate of 10 2 s I, to about 65% at the nominal rate of 10-5 s-I. The delayed elastic component of the strain increased with decreasing strain rate and there was a significant plastic component at the nominal rate of 10 5 s I (Gold, 1994). In summary, the occurrence of the maxima ",,'ith decreasing strain rate is associated with an increasing proportion of trans crystalline cracks and an increasing delayed elastic and plastic strain.…”
Section: Spatial Distributionmentioning
confidence: 89%